Biovalorisation of food waste in Singapore : synergistic effect of a mixed culture in solid-state fermentation - Ong, Adwin Reng Jun (Nanyang Technological University, 2021)
Okara and brewer’s spent grain (BSG) are manufacturing side streams produced in massive amounts from the soy and beer industries, respectively, and contributes significantly to food waste. However, these materials are still nutritious and can be repurposed for farming and food applications through nutritional profile enhancement using biovalorisation. In this study, solid-state fermentation (SSF) was performed using okara and BSG as substrates to investigate the effects of fermentation using pure and mixed cultures of Aspergillus oryzae and Bacillus subtilis. The synergistic effect of cooperative metabolism in mixed cultures was also studied. The total phenolic content (TPC), crude protein content, and total dietary fibre (TDF) of the fermented substrates were determined after fermentation to evaluate their nutritional profiles. Okara fermented with a mixed culture under specific conditions produced the highest TPC of 1100 mg/100g dry matter, which was more than 13 times that of the control. Its TDF profile was also the most ideal, striking a good balance between IDF and SDF reduction. These results reflected the presence of cooperative metabolism between Aspergillus oryzae and Bacillus subtilis during fermentation, which afforded greater enhancement in the nutritional profile of substrates compared to that of pure cultures. However, the crude protein content of the samples could not be accurately determined due to the formation of volatile nitrogenous compounds and loss of dry matter during fermentation. Competition between Aspergillus oryzae and Bacillus subtilis in samples containing BSG also impeded the progress of fermentation. More specific methods of protein quantification and optimisation of sample preparation for BSG in future work is recommended. In this study, mixed cultures in SSF has shown great promise, and further research of this methodology will facilitate its use and development in future applications.